A privátszféra polgári jogi védelmének alapkérdései - Fézer, Tamás (Debreceni Jogi Műhely, 2014)
Privacy has become a hot topic in personality rights protection in the 21st century all over the world. Classic personality rights did not cover all aspects of modern privacy law and the lack of an exhaustive list for personality rights also left many questions unanswered. The right to privacy is hard to define and it is even more difficult to identify the limits of this sensitive right. Our goal is to analyze various definitive attempts to privacy and synthetize them with actual judicial practice in order to get closer to what privacy law truly covers in modern jurisdictions. Even if brand new challenges arise almost every day, privacy remains a powerful instrument to provide autonomy to individuals and sometimes to legal entities.